Identifying populations of the marble goby, oxyeleotris marmorata (Bleeker, 1852) by otolith shape analysis and their spawning seasons in Likas Bay, Sabah, Malaysia - Gunzo Kawamura; Yong, Annita Seok Kian; Difa Dhaniah Zharfan Engcong; Kai Ying Chieng; Audrey Daning Tuzan; Lim, Leong-Seng (Borneo Marine Research Institute, 2024)
The marble goby, Oxyeleotris marmorata is native to fresh and brackish waters of Southeast Asia. The yield of wild O. marmorata has been decreased drastically and urgent conservation actions are required to prevent extinction. In the Likas Bay, Oyeleotris marmorata is caught throughout the year by local fishermen using various fishing gears. In fisheries management, population is a fundamental biological unit and population identification of a species is important. The population structure of this marine stock was determined by otolith shape analysis and their spawning season in the Likas Bay was determined by ovarian observations. A total of 147 specimens were procured between 2018 and 2019; size ranged from 443 g to 3,264 g BW. The curvature index of the otoliths was analyzed by Bhattacharya’s method and found that the frequency distribution of curvature indices is a mixture of two normal components, indicating two different populations. The specimens with mature or spent ovaries were found in samples collected in January – February and September, showing two spawning seasons. The age of each specimen was estimated by counting the vertebral annuli. The estimated age ranged from 5 to 14 years. The minimum size and age of spawners was 338 mm TL, 499 g BW and 5 years old. The findings obtained in this study provide basic biological parameters of O. marmorata populations in Likas Bay